Komitmen Manajemen dan Safety Procedure sebagai Faktor Pembentuk Safety Behavior - Jarman Setiadi; Masdzulhak Masdzulhak; Dudi Permana; Erna Sofriana Imaningsih (Universitas Faletehan, 2023)
The globalization of trade nowadays impacts on an extremely fierce industry competition in all aspects and requires companies to more optimize all their resources. In addition to optimizing labor resources, companies also need to optimize the use of machines and work equipment to guarantee workers’ safety and health. This research aimed to test the role of safety cultures as the factor mediating the influence of management commitment and safety procedures to safety behaviors. The research method was quantitative with the sample size of 117 workers as the respondents. The instrument test of hypothesis was Smart PLS (Partial Least Squares). The results showed that management commitment influenced safety cultures as much as 27.84%; safety procedures influenced on safety cultures by 20.59%; and the influence of safety cultures on safety behaviors was 38.40%. In contrast, management commitment and safety procedures did not affect safety behaviors. The researcher concluded that safety cultures can mediate the influence of management commitment toward safety procedures and safety behaviors.